MECHANISM FOR FORMING AN EFFECTIVE PORTFOLIO OF RESEARCH PROJECTS OF INSTITUTION OF HIGHER EDUCATION - Varvara Piterska; Oleh Lohinov; Liliia Lohinova (Сучасний стан наукових досліджень та технологій в промисловості, 2019)
The subject matter of the article is the methods, models and mechanisms of forming a portfolio of research projects of higher education institutions. The goal of the work is to develop a mechanism for managing a portfolio of research projects of a higher education institution based on the commercialization of the results of scientific activities of the university based on a risk management system. The following tasks were solved in the article: analysis of the scientific management model of higher education institutions, the study of modern methods of managing portfolios of research projects of universities, the development of a mechanism for the formation of an effective portfolio of research projects of higher education institutions taking into account risks and the commercialization of scientific results. The following methods used are – project and portfolio management methods, systems theory and systems analysis, risk management methods. The following results were obtained – the mechanism for creating a portfolio of research projects taking into account the strategic goals of a higher education institution was developed, a consolidated plan for the implementation of scientific projects of a portfolio was created, a mechanism for managing a portfolio of research projects of a higher education institution was developed based on a grouping of projects according to risk criteria and the commercialization of scientific results. Conclusions: using the portfolio management mechanism will allow higher education institutions to form balanced portfolios of scientific projects, thereby more effectively implementing innovative programs taking into account risk criteria and the commercialization of scientific results. The most difficult task of the scientific project management system is the task of forming a portfolio of research projects. The portfolio of research projects of a higher education institution is valuable if it allows you to develop activities aimed at creating and strengthening competitive advantages. However, the university’s capabilities in terms of forming a portfolio of research projects are limited by available resources, as well as by the increasing complexity of developing the latest technologies that require the involvement of third-party organizations, because the possibilities of establishing a higher education for independent conduct and processing of the results of scientific activities are limited. At the stage of selection of research projects, a list of current projects is formed; an analysis of research projects in the portfolio is carried out for compliance with the strategic goals of the institution of higher education. By grouping research projects in a portfolio and forming the necessary criteria for the projects to correspond to a particular group (direction) of scientific research, the projects are linked both with each other and with the goals of a higher education institution, and the transparency of the formed portfolio of research projects is increased. At the stage of balancing research projects, resources are allocated in accordance with the directions of research projects and the objectives of the portfolio of projects of higher education institutions. At the same time, the portfolio should increase the share of research projects with high value for higher education institutions and the share of projects designed to bring higher education institutions dividends from the commercialization of scientific results (patent implementation) and reduce the share of high-cost research projects, as well as projects with high risks. The following criteria are used as the main criteria in balancing the portfolio of research projects of higher education institutions in work: expenses for the implementation of research projects; the value of projects for higher education institutions; project risk; proportion of projects in the portfolio.